PERBANDINGAN KONSUMSI DAYA BATERAI LI-ION 18650 DENGAN LIFEPO4 32700 BERDASARKAN JARAK TEMPUH - Yusuf, Alvatoni Achmad (Jurnal Energi Dan Manufaktur; Vol 16 No 2 (2023), 2023)
Air pollution is increasing due to emissions from fossil fuel motor vehicles so that electric vehicles are one of the solutions to reduce pollution produced from vehicles. The increase in electric vehicles makes the need for sources of electrical energy increase. Solar panels are an alternative source of renewable electrical energy. Utilization of solar energy requires a battery that functions as energy storage. This research was tested at a distance of 100 meters at a stable speed of 19.78km/h. The results of the test will be read with a data logger system consisting of a voltage sensor, current sensor, speed sensor with Arduino UNO as a microcontroller and Micro SD as a storage medium and an LCD display to display data as a reference during testing in real time. The results of this study are, with the same distance and speed, the total power consumption of LiFePo4 batteries is on average 305.13W greater than Li-Ion. With an average power consumption of 86.17W for LiFePo4 and 69.22 W for Li Ion. Li Ion batteries have the advantage of longer battery life due to less power consumption. Meanwhile, LiFePo4 batteries have the advantage of producing higher power so that vehicle performance is also more optimal, as well as better current and voltage stability which results in more stable power consumption. Keywords: Lithium Ion battery, LiFePO4 battery, transport e-scooter